OPTIMALISASI PERAN KADER POSYANDU TERHADAP PENCEGAHAN STUNTING DI DUSUN PAMEUNGPEUK DESA CIKAHURIPAN SUKABUMI - Elza Nurhalizah Rahmadini; Ismi Asri Nur Qoyumi, Muhammad Akmal Bismoyo, Nurul Fania, Raka Febrianto, Shabrina Putri Syarafah (CV. ADIBA AISHA AMIRA, 2024)
Stunting is the main problem faced by the Indonesian government as well as being the main focus in improving the nutrition of the nation's children. The problem of stunted children (stunting) is a result of the lack of nutritional intake status of mothers and children. The nutritional status and health of the mother during pre-pregnancy, during pregnancy, and during breastfeeding since the first 1000 days of life (HPK) are very critical period. Thus, chronic malnutrition in 1000 HPK will have an impact on physical growth disorders, one of which is stunting. The problem of stunting is inseparable from community nutrition problems that are associated with an increased risk of death, illness, and both motor and mental problems, so that it has an impact on uncompetitive work quality which results in low levels of income and community welfare. Therefore, the Indonesian government is committed to the prevention and reduction of stunting prevalence. Cikahuripan Village, to be precise in Pameungpeuk Hamlet, is one of the hamlets that has stunting cases in children. Integrated Service Post (Posyandu) as a health service in the hamlet has an important role in reducing the prevalence of stunting. By using the Participatory Rural Appraisal (PRA) technique and the qualitative method of direct interviews, it was found that optimizing the role of cadres is important for the modality of community empowerment, especially in the health and nutrition sector.